Yttrium-based coating film and method for producing same
By forming high-hard yttrium oxide and yttrium fluoride films, the problem of insufficient hardness of the existing yttrium fluoride spray coating films has been solved, and the hardness, corrosion resistance, wear resistance and dust generation resistance have been improved. It is suitable for High performance component surface.
Patent Information
- Application Number
- CN202380045226.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-11
- Filing Date
- 2023-10-06
- Publication Date
- 2025-01-17
AI Technical Summary
The existing yttrium fluoride spray coating has a maximum Vickers hardness of 560HV, which cannot meet the needs of higher hardness.
By forming a yttrium oxide film and yttrium oxide film with a Vickers hardness of more than 900 HV, X-ray diffraction and SEM analysis are used to ensure the optimization of the crystal structure, including the preferential orientation of the (222) plane and (151) plane and the high diffraction intensity. And the film is formed by the PVD method, the CVD method and the ion beam-assisted evaporation method.
It realizes an yttrium-based film with excellent hardness, improves corrosion resistance, wear resistance and dust generation resistance, and is suitable for component surfaces that require high performance.
Smart Images

Figure CN119325524A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an yttrium-based film containing yttrium oxide and yttrium oxyfluoride and a method for producing the same. Background Art
[0002] As such a yttrium-based film, a film of an yttrium fluoride-based sprayed film is known to be obtained by plasma spraying a spraying powder containing an orthorhombic YF3 crystal phase and containing no YF3 crystal phase other than an orthorhombic crystal phase (see Patent Document 1).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent No. 7306490 Summary of the invention
[0006] Problems to be solved by the invention
[0007] However, the Vickers hardness of the conventional yttrium fluoride-based thermal sprayed film is 560 HV at most, and further improvement in hardness is required.
[0008] The problem to be solved by the present invention is to provide an yttrium-based film having excellent hardness and a method for producing the same.
[0009] Means for solving problems
[0010] The present invention solves the above-mentioned problems by providing an yttrium oxide film having a Vickers hardness of 900 HV or more.
[0011] In the above invention, it is more preferable that the half-value width of the (222) plane of the yttrium oxide crystal based on X-ray diffraction is 0.7° or more.
[0012] In the above invention, it is more preferable that the (222) plane is preferentially oriented in the crystal structure of yttrium oxide.
[0013] In the above invention, it is more preferable that the diffraction intensity of the (222) plane in X-ray diffraction is at least twice that of other crystal planes.
[0014] In the above invention, it is more preferable that the film is formed on the surface of a member requiring corrosion resistance, wear resistance, dust generation resistance, and the like.
[0015] In the above invention, the film can be formed by any one of PVD, CVD, and ALD, and is more preferably formed by ion beam assisted deposition.
[0016] In addition, the present invention solves the above-mentioned problems by using an yttrium oxyfluoride film having a Vickers hardness of 900 HV or more.
[0017] In the above invention, it is more preferable that, when surface analysis is performed by SEM, the surface of the yttrium oxyfluoride crystal is dominated by particles having a particle size of 50 nm to 300 nm.
[0018] In the above invention, it is more preferable that, when surface analysis is performed by SEM, the surface of the yttrium oxyfluoride crystal has a shape in which particles having a particle size of 50 nm to 300 nm and particles having a particle size of 5 nm to 20 nm located on the particles are doubly formed.
[0019] In the above invention, it is more preferred that, when cross-sectional analysis is performed by SEM, for the cross-section of the yttrium oxyfluoride crystal, the fibrous cross-sectional structure with a lateral width of 20nm to 50nm and a length of more than 200nm in the thickness direction is not dominant, and a blocky columnar structure with a particle size of more than 100nm is observed.
[0020] In the above invention, it is more preferable that the half value width of the (151) plane of the yttrium oxyfluoride crystal based on X-ray diffraction is 0.5° or more.
[0021] In the above invention, it is more preferable that the (151) plane is preferentially oriented in the crystal structure of yttrium oxyfluoride.
[0022] In the above invention, it is more preferable that the diffraction intensity of the (151) plane in X-ray diffraction is at least twice that of other crystal planes.
[0023] In the above invention, it is more preferable that the film is formed on the surface of a member that requires at least corrosion resistance, wear resistance, and dust generation resistance. Examples of the material of these members include aluminum, quartz, sapphire, ceramics, and the like.
[0024] In the above invention, the film can be formed by any one of PVD, CVD, and ALD, and is more preferably formed by ion beam assisted deposition.
[0025] In the above invention, when forming the above film, a period of time in which film formation is performed and a period of time in which film formation is not performed may be repeated intermittently.
[0026] Effects of the Invention
[0027] According to the present invention, a film having excellent hardness can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a graph showing the characteristics of the yttrium oxide film of Example 1 of the present invention and Comparative Example 1.
[0029] Figure 2AThis is a diagram showing the characteristics of the yttrium oxyfluoride films of Examples 2 and 3 of the present invention and Comparative Example 2 (Part 1).
[0030] Figure 2B This is a diagram showing the characteristics of the yttrium oxyfluoride films of Examples 2 and 3 of the present invention and Comparative Example 2 (part 2).
[0031] Figure 3 This is a conceptual diagram showing the relationship between the hardness and crystallinity of an yttrium oxyfluoride film.
[0032] Figure 4 It is a schematic cross-sectional view showing the crystal structure of Example 2 (yttrium oxyfluoride film having high hardness) of the present invention.
[0033] Figure 5 It is a schematic cross-sectional view showing the crystal structure of Comparative Example 2 (yttrium oxyfluoride film having low hardness) of the present invention. DETAILED DESCRIPTION
[0034] Hereinafter, embodiments of the present invention will be described based on the drawings.
[0035] "Yttrium Oxide Film"
[0036] The hard film of the film of the present invention having a Vickers hardness of 900 HV or more is an yttrium oxide film, the half-value width of the (222) plane of the yttrium oxide crystal based on X-ray diffraction is more than 0.7°, the (222) plane is preferentially oriented in the crystal structure of yttrium oxide, and the diffraction intensity of the (222) plane in X-ray diffraction is more than twice that of other crystal planes. It can be formed on the surface of parts requiring corrosion resistance, wear resistance, dust generation resistance, etc., and the film can be formed by any one of PVD method, CVD method, and ALD method.
[0037] In addition, the hard film of the film of the present invention having a Vickers hardness of 900 HV or more is an yttrium oxyfluoride film. When the surface is analyzed by SEM, for the surface of the yttrium oxyfluoride crystal, a shape in which particles having a particle size of 50 nm to 300 nm and particles having a particle size of 5 nm to 20 nm further located on the particles are formed in a double manner is dominant. When the cross-sectional analysis is performed by SEM, for the cross-sectional analysis of the yttrium oxyfluoride crystal, a fibrous structure having a lateral width of 20 nm to 50 nm and a thickness direction length of 200 nm or more is formed. The cross-sectional structure is not dominant, and a blocky columnar structure with a particle size of more than 100 nm is observed. The half-value width of the (151) plane of the yttrium oxyfluoride crystal based on X-ray diffraction is more than 0.5°. In the crystal structure of yttrium oxyfluoride, the (151) plane is preferentially oriented, and the diffraction intensity of the (151) plane in X-ray diffraction is more than twice that of other crystal planes. It can be formed on the surface of parts that require corrosion resistance, wear resistance, dust generation resistance, etc., and can form a film by any of the PVD method, CVD method, and ALD method.
[0038] Example
[0039] Hereinafter, the present invention will be described in more detail with reference to examples and comparative examples of the present invention, but the present invention is not limited in any way to the conditions and results of these examples.
[0040] 《Example 1 and Comparative Example 1 (Yttrium Oxide Film)》
[0041] An ion beam assisted vacuum deposition apparatus (EPD manufactured by Shincolon Corporation) was used, and the deposition source was yttrium oxide Y2O3. The film was formed on the surface of a sapphire substrate at a film forming rate of 0 to 10 angstroms / second (excluding both ends) by irradiation / non-irradiation with an ion beam. The films obtained by combining different film forming conditions were referred to as Example 1 and Comparative Example 1.
[0042] The Vickers hardness of each of the films of Example 1 and Comparative Example 1 was measured using a Vickers hardness tester (manufactured by BRUKER Co., Ltd.), a SEM photograph of the film surface was taken using a scanning electron microscope (manufactured by JEOL Ltd.), and the crystallinity of the film was confirmed using an X-ray diffraction apparatus (manufactured by Rigaku Co., Ltd.). Figure 1 The characteristics of the yttrium oxide films of Example 1 and Comparative Example 1 are shown in FIG. Figure 1 In the figure, "Hardness HV" represents Vickers hardness, "Surface SEM photograph" represents a photograph of the film surface based on a scanning electron microscope, "XRD spectrum" represents diffraction intensity-diffraction angle based on an X-ray diffraction device, "XRD2θ" represents the diffraction angle of X-ray diffraction (θ is the Bragg angle), and "XRD half-value width" represents the half-value width at a diffraction angle of 2θ.
[0043] If Figure 1 Compared with the hardness shown in the figure, the hardness of Example 1 is 993HV, which is higher than the hardness of Comparative Example 1. Figure 1 Compared with the SEM photos shown in FIG. 1 , the surface of Example 1 is smoother than that of Comparative Example 1. Figure 1 By comparing the X-ray diffraction spectrum, diffraction peak and half-value width of the diffraction peak, it is confirmed that the (222) plane of the yttrium oxide crystal has a diffraction peak near the diffraction angle 2θ=29°. In Example 1, the diffraction peak of the (222) plane with a diffraction angle 2θ≈29° is more than twice the diffraction intensity of other crystal planes, and the half-value width of the diffraction peak of the (222) plane is also as large as 0.7° or more. From these results, it can be confirmed that in the crystal structure of the yttrium oxide constituting the film of Example 1, the (222) plane is preferentially oriented.
[0044] 《Examples 2, 3 and Comparative Example 2 (Yttrium Oxyfluoride Film)》
[0045] An ion beam assisted vacuum deposition apparatus (MIC manufactured by Shin-Colon Corporation) was used, and the two deposition sources were yttrium oxide Y2O3 and yttrium fluoride YF3. On the surface of a quartz substrate, the total film forming rate of yttrium oxide Y2O3 and yttrium fluoride YF3 was set to a range of 0 to 10 angstroms / second (excluding both ends), and the film forming rate ratio of yttrium oxide Y2O3 / yttrium fluoride YF3 was set to a range of 10% to 90%, and the film was formed by irradiation / non-irradiation with ion beams. The films obtained under different film forming conditions were designated as Examples 2 and 3 and Comparative Example 2. It should be noted that Example 3 is an example of film formation while repeating the film forming time and the non-film forming time intermittently in order to suppress the substrate temperature from being overheated to a predetermined temperature during film formation.
[0046] For each of the films obtained in Examples 2, 3 and Comparative Example 2, the Vickers hardness was measured using a Vickers hardness tester (manufactured by BRUKER Co., Ltd.), SEM photographs of the film surface were taken using a scanning electron microscope (manufactured by JEOL Ltd.), and the crystallinity of the film was confirmed using an X-ray diffraction apparatus (manufactured by Rigaku Co., Ltd.). Figure 2A and Figure 2B The characteristics of the yttrium oxyfluoride films of Examples 2 and 3 and Comparative Example 2 are shown in FIG. Figure 2A In the figure, "Hardness HV" indicates Vickers hardness, "Surface SEM Photograph" indicates a photo of the surface of the film taken by a scanning electron microscope, and "Cross-Section SEM Photograph" indicates a photo of the cross-section of the film taken by a scanning electron microscope. Figure 2B In the figure, “XRD spectrum” represents the diffraction intensity-diffraction angle based on an X-ray diffraction device, “XRD2θ” represents the diffraction angle of X-ray diffraction (θ is the Bragg angle), and “XRD half-value width” represents the half-value width at the diffraction angle of 2θ.
[0047] If Figure 2A Compared with the hardness shown in the figure, the hardness of Example 2 is 996HV, and the hardness of Example 3 is 899HV. The hardness of Examples 2 and 3 is higher than that of Comparative Example 2. Figure 2A Compared with the surface SEM photos shown in the figure, the surfaces of Examples 2 and 3 are smoother than the surface of Comparative Example 2. Figure 2B Compared with the cross-sectional SEM photographs shown, the cross-section of the membrane of Comparative Example 2 is a fibrous cross-sectional structure with a lateral width of 20nm to 50nm and a length of more than 200nm in the thickness direction. In contrast, the cross-sectional structure of the membranes of Examples 2 and 3 is not such a fibrous cross-sectional structure, but a cross-sectional structure with particles having a particle size of 50nm to 300nm and particles of 5nm to 20nm further located on the particles.
[0048] Furthermore, if Figure 2BBy comparing the X-ray diffraction spectra, diffraction peaks and half-widths of the diffraction peaks, the (151) plane of the yttrium oxyfluoride crystal shows a diffraction peak near the diffraction angle of 2θ=28°, and the diffraction intensity of the (151) plane with a diffraction angle of 2θ≈28° is more than twice that of the diffraction intensity of other crystal planes. However, the half-width of the diffraction peak of the (151) plane of Example 2 is 0.69°, and the half-width of the diffraction peak of the (151) plane of Example 3 is 0.57, both of which are larger than the half-width of the diffraction peak of the (151) plane of Comparative Example 2 of 0.28.
[0049] Figure 3 This is a conceptual diagram showing the relationship between the hardness of the film and the size of the crystal. The crystal structure observed by SEM is correlated with the hardness of the film, such as Figure 3 As shown in the figure, the larger the crystals of the film, the higher the hardness. Generally, it can be said that the corrosion resistance and wear resistance of the film with high hardness are excellent. In addition, the surface of the film with high hardness is smoother than that of the film with low hardness. Generally, the smoother the surface and the higher the hardness, the more difficult the film is to cut, so it can be said that the dust generation resistance is excellent.
[0050] Figure 4 and Figure 5 is a schematic cross-sectional view of a film showing the relationship between the hardness of the film and the crystal structure. Figure 4 Example 2 is shown. Figure 5 Comparative Example 2 is shown. Figure 4 As shown in FIG. 1 , in the high hardness yttrium oxyfluoride film of 900 HV or more, the film crystal structure in which particles of 5 nm to 20 nm are further stacked on a blocky columnar structure of 50 nm to 300 nm in diameter is dominant. Figure 5 As shown, in the low-height yttrium oxyfluoride film of 400 HV or less, a fibrous cross-sectional structure having a lateral width of 20 nm to 50 nm and a thickness length of 200 nm or more is dominant.
[0051] From the perspective of corrosion resistance of the film, it is preferred that the film has fewer grain boundaries, i.e., fewer columnar crystal interfaces. This is because there is a concern that corrosive gases, etc., may erode through the gaps between the grain boundaries and reach the substrate, etc. In addition, from the perspective of wear resistance or resistance to dust generation, the surface shape of the film is preferably smooth. This is because when fine needle-shaped irregularities are formed on the surface, the needle-shaped irregularities are easily worn and can become a source of dust generation. If these aspects are evaluated Figure 4 and Figure 5 The membrane is compared with Figure 5 The film of Comparative Example 2 shown, Figure 4 The film of Example 2 shown exhibits film characteristics excellent in corrosion resistance, wear resistance, and dust generation resistance from the perspective of the crystal structure.
Claims
1. An yttrium oxide film having a Vickers hardness of 900 HV or more.
2. An yttrium oxide film, wherein: The half-value width of the (222) plane of the yttrium oxide crystal based on X-ray diffraction is 0.7° or more.
3. An yttrium oxide film, wherein: In the crystal structure of yttrium oxide, the (222) plane is preferentially oriented.
4. The yttrium oxide film according to claim 3, wherein The diffraction intensity of the (222) plane in X-ray diffraction is more than twice that of other crystal planes. 5 . The yttrium oxide film according to claim 1 , which is formed on the surface of a member that requires at least corrosion resistance, wear resistance, or dust generation resistance. 6 . A method for producing an yttrium oxide film, comprising forming the film according to claim 1 by any one of PVD, CVD, and ALD. 7 . A method for producing an yttrium oxide film, comprising forming the film according to claim 1 by ion beam assisted deposition.
8. An yttrium oxyfluoride film having a Vickers hardness of 900 HV or more.
9. An yttrium oxyfluoride film, wherein: When the surface was analyzed by SEM, the surface of the yttrium oxyfluoride crystal was dominated by particles having a particle size of 50 nm to 300 nm.
10. An yttrium oxyfluoride film, wherein: When the surface was analyzed by SEM, the surface of the yttrium oxyfluoride crystal was dominated by a shape in which particles having a particle size of 50 nm to 300 nm and particles having a particle size of 5 nm to 20 nm located on the particles were formed in duplicate.
11. An yttrium oxyfluoride film, wherein: When cross-sectional analysis was performed by SEM, the cross-sectional structure of the yttrium oxyfluoride crystal was not dominant, and a massive columnar structure with a particle size of 100 nm or more was observed instead.
12. An yttrium oxyfluoride film, wherein: The half-value width of the (151) plane of the yttrium oxyfluoride crystal based on X-ray diffraction is 0.5° or more.
13. An yttrium oxyfluoride film, wherein: In the crystal structure of yttrium oxyfluoride, the (151) plane is preferentially oriented.
14. The yttrium oxyfluoride film according to claim 13, wherein The diffraction intensity of the (151) plane in X-ray diffraction is more than twice that of other crystal planes. 15 . The yttrium oxyfluoride film according to claim 8 , which is formed on the surface of a member that requires at least corrosion resistance, wear resistance, or dust generation resistance. 16 . A method for producing an yttrium oxyfluoride film, comprising forming the film according to claim 8 by any one of PVD, CVD and ALD. 17 . A method for producing an yttrium oxyfluoride film, comprising forming the film according to claim 8 by ion beam assisted deposition.
18. The method for producing an yttrium oxyfluoride film according to claim 16 or 17, wherein: When the film is formed, a period of time in which film formation is performed and a period of time in which film formation is not performed are repeated intermittently.